Lifestyle can exert a significant impact on the development of metabolic comorbidities in early-stage colorectal cancer patients - Xin, Yu; Liu, Chunxia; Cui, Jianfang; Wang, Yanan; Wu, Honglei (Frontiers in Nutrition, 2025)
BackgroundMetabolic dysregulation has been identified as contributing to colorectal cancer (CRC) development. However, there is a lack of data regarding the association between lifestyle factors and metabolic diseases in CRC patients.MethodsWe conducted a multi-center cross-sectional study including 437 early-stage CRC patients and 437 control participants between April 2023 and March 2024. The dietary inflammatory index (DII) was calculated based on dietary data, which was collected using a food frequency questionnaire. A healthy lifestyle was defined as adherence to an anti-inflammatory diet (DII score < 0) combined with active physical activity.ResultsAmong early-stage CRC patients, overweight and obesity were associated with an anti-inflammatory diet (OR = 0.585, 95% CI = 0.346–0.988, p = 0.045; OR = 0.463, 95% CI = 0.221–0.966, p = 0.040). Metabolic syndrome (MS) was associated with overweight or obesity (OR = 2.203, 95% CI = 1.283–3.782, p = 0.004) and age (OR = 1.052, 95% CI = 1.030–1.073, p < 0.001). Type 2 diabetes mellitus (DM2) or prediabetes was associated with overweight or obesity (OR = 1.788, 95% CI = 1.079–2.960, p = 0.024) and age (OR = 1.053, 95% CI = 1.032–1.073, p < 0.001). Metabolic dysfunction-associated fatty liver disease (MAFLD) was associated with overweight or obesity (OR = 1.807, 95% CI = 1.122–2.910, p = 0.015), age (OR = 1.039, 95% CI = 1.020–1.058, p < 0.001), and an unhealthy lifestyle (OR = 4.314, 95% CI = 1.549–12.014, p = 0.005). Moreover, both an active lifestyle and a healthy lifestyle were significantly associated with a lower likelihood of being diagnosed with overweight or obesity, MS, DM2 or prediabetes, and MAFLD (p < 0.05). Stratified analysis revealed that late-onset CRC patients adhering to an active lifestyle and a healthy lifestyle showed risk reductions for these metabolic comorbidities (p < 0.05).ConclusionAdherence to healthy lifestyles, particularly in individuals aged ≥50 years, may alleviate metabolic dysregulation in early-stage CRC patients.